The improvent of student creavity in entrepreneurial subject through think,write, and talk model. - Zurika, Henny (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Ing and learning process of entrepreneurship through think,write,and talk learning model. This study aims to improve the quality of the process and result of result of student learning which were previously known to less meet learning expectations . This study was conducted to students of class VII A in accounting education of UMSU in the Odd semester of 2015/2016 Academic Year ,in total of 30 people.